Growth Of Halal Attraction In Kediri: Maqashid Syariah Perspectives and DSN-Mui Fatwa No. 108/2016 - Siti Nur Mahmudah; Ishfaq Ahmed (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Syekh Wasil Kediri, 2025)
This study aims to investigate how the DSN-MUI Fatwa No. 108/DSN-MUI|X|2016 has been applied in the development of halal tourism attractions in Kediri City, with an emphasis on Maqashid Syariah. Qualitative research methods. The DSN-MUI Fatwa No. 108/DSN-MUI|X|2016 has positively impacted the expansion of halal tourism destinations in Kediri, according to the study's findings. The development of halal tourism infrastructure, the provision of halal accommodation, halal food alternatives, halal entertainment and activities, and halal marketing and promotion have all seen notable improvements. This execution has improved Kediri's appeal as a halal tourism destination, met the needs of Muslim tourists, and contributed to the social and economic development of the city. From the perspective of Maqashid Syariah, Kediri City's utilization of halal tourism destinations has been effective in meeting three different kinds of needs: primal (Hifz al-Din, Hifz al-Nafs), logical (Hifz al-Aql), and moral and ethical (Hifz al-Nasl, Hifz al-Mal).